POLITENESS STRATEGIES USED BY THE PRESIDENTIAL CANDIDATES OF INDONESIA IN THE 2019 PRESIDENTIAL DEBATES - Meida Rabia Sihite; Sofia Idawati Lubis; Devi Meitina Astuty Silalahi (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
Presidential debate is one of an interesting examples to be analyzed in terms of politeness strategies. This research analyzed the politeness strategies used by the presidential candidates of Indonesia in a presidential debate program during the election period in 2019. This research employed qualitative descriptive. The data were in the form of spoken utterances which were collected from the debate participants. The sources of the data in this research were the videos and transcripts of the second and the fourth presidential debates taken from youtube and google. The data were analyzed using data condensation, data displayed, drawing and verifying conclusion. The results of the research showed that the presidential candidates used several types of politeness strategies and realizations of politeness. There were four types of politeness strategies found in the debates; they were Bald-On Record, Positive Politeness, Negative Politeness, and Off Record. In realizations of politeness strategies, there were 30 sub-strategies realized in the second debate and 33 sub-strategies realized in the fourth debate. Positive Politeness was found as the dominant strategy since the candidates wanted to omit any gaps, give good sense, choose words selectively and convey their campaign.